Students’ gratitude and engagement in online learning: An experimental study - Qudsyi, Hazhira; Wijaya, Hariz Enggar; Rusdi, Ahmad; Rachmawati, Mira Aliza; Nu’man, Thobagus Muhammad (International Journal of Innovative Research and Scientific Studies, 2024)
Engagement is essential in education, particularly in online learning. Many studies have been done to determine various antecedents of student engagement. However, more evidence-based experimental research is still needed to improve student engagement during online learning. This study aims to examine the effect of a gratitude intervention on student engagement in online learning. This study uses an experimental research design with a pre-and post-test control group design. Two online questionnaires were used in this study, a gratitude adjective checklist (GAC) and an online student engagement scale (OSES) which were administered to 47 undergraduate students. The participants were classified randomly into three conditions. In the first group, 20 students had a general gratitude exercise (experimental Group 1). In the second group, 15 students had an Islamic gratitude task (experimental Group 2). The last group consisted of 12 students without any gratitude tasks as a control group. The data were analyzed with Anova repeated measurements based on the pre- and post-test control group design. Results showed no interaction between different types of treatment and increased online engagement. However, it was found that the general gratitude treatment had the most significant effects compared to other treatments. This research proves that students can increase student engagement through the habit of being grateful daily including by writing down what things make them grateful.